2020
DOI: 10.3390/jcm9103236
|View full text |Cite
|
Sign up to set email alerts
|

CoQ10 Deficient Endothelial Cell Culture Model for the Investigation of CoQ10 Blood–Brain Barrier Transport

Abstract: Primary coenzyme Q10 (CoQ10) deficiency is unique among mitochondrial respiratory chain disorders in that it is potentially treatable if high-dose CoQ10 supplements are given in the early stages of the disease. While supplements improve peripheral abnormalities, neurological symptoms are only partially or temporarily ameliorated. The reasons for this refractory response to CoQ10 supplementation are unclear, however, a contributory factor may be the poor transfer of CoQ10 across the blood–brain barrier (BBB). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 84 publications
0
13
0
1
Order By: Relevance
“…Once diagnosed, patients with CoQ deficiency respond well to high dose oral CoQ supplementation, although early diagnosis and treatment is essential to ensure an optimal clinical response [ 104 ]. Whilst CoQ supplementation appears to improve peripheral abnormalities, neurological symptoms appear to be more refractory to treatment and this may reflect the limited ability of CoQ to cross the blood–brain barrier [ 108 ]. A deficit in CoQ status has been reported in neurological disorders, resulting in antioxidant status disturbances and mitochondrial dysfunction frequently leading to severe neuronal degeneration [ 109 , 110 ].…”
Section: Other Clinical Aspectsmentioning
confidence: 99%
“…Once diagnosed, patients with CoQ deficiency respond well to high dose oral CoQ supplementation, although early diagnosis and treatment is essential to ensure an optimal clinical response [ 104 ]. Whilst CoQ supplementation appears to improve peripheral abnormalities, neurological symptoms appear to be more refractory to treatment and this may reflect the limited ability of CoQ to cross the blood–brain barrier [ 108 ]. A deficit in CoQ status has been reported in neurological disorders, resulting in antioxidant status disturbances and mitochondrial dysfunction frequently leading to severe neuronal degeneration [ 109 , 110 ].…”
Section: Other Clinical Aspectsmentioning
confidence: 99%
“…However, no assessment was undertaken on the cerebral inflammatory response following CoQ10 supplementation. At present, it is uncertain whether CoQ10 is able to cross the blood-brain barrier (BBB) of humans, and a study by Wainwright et al [ 91 ] has added further support to this supposition. However, in this study, it was suggested that uptake of exogenous CoQ10 into the brain may be enhanced by the administration of LDLR inhibitors, or by interventions to stimulate the luminal activity of the Scavenger Receptor, SR-B1 transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in view of the important role CoQ 10 plays as an electron carrier in the ETC and as a potent antioxidant, we cannot at present exclude the potential for CoQ 10 to elicit significant enhancement of mitochondrial functioning in the CNS disorders discussed in this review [15,45]. However, a lack of improved neurological outcome post treatment with CoQ 10 may be attributable to the limited ability of CoQ 10 to cross the BBB [94]. There is still uncertainty about the transports of CoQ 10 across the BBB in humans and to date, no studies to date have yet assessed the transport of CoQ 10 across the human BBB.…”
Section: Expert Opinionmentioning
confidence: 91%
“…Yet, it is unclear whether this increase in CoQ 10 status following supplementation would be sufficient to replenish an underlying cerebral CoQ 10 deficiency. An in vitro study assessing the transport of CoQ 10 across the BBB has reported that the uptake of CoQ 10 via the Receptor for Advanced glycation end products (RAGE) and SR-B1 (scavenger Receptor) correlates with an efflux via the low-density lipoprotein receptor (LDLR) transporters, demonstrating that CoQ 10 transcytosis occurs in both directions, resulting in no 'net' transport across the BBB [94]. In view of this, administration of LDLR inhibitors or the stimulation of the luminal activity of SR-B1 transporters in conjunction with CoQ 10 supplementation may be an appropriate method to enhance the CNS uptake of exogenous CoQ 10 .…”
Section: Expert Opinionmentioning
confidence: 99%